Evaluación de salmueras, tiempos y temperaturas de ahumado en la conservación de la carne de codorniz (Coturnix Coturnix Japónica). - Suárez Suárez, Vanessa Marlene (2013)
The present investigative work was carried out in the Experimental Property “The María” in the facilities of the Plant of Meat of the Ability of Cattle Sciences of the State Technical University of Quevedo (U.T.E.Q), located in the km. 7 of the road Quevedo-The Connection, county of The Ríos, the geographical location is of 1º 6° 2 30° of south latitude 79º 29 30° of longitude west and to a height of 124 msnm. The investigation was carried out among the months of January to May of the 2011. 128 quails were used, of 30 to 48 days of age with different pesos; each experimental unit conformed to for 4 quails, having eight treatments and four repetitions, therefore one worked with 128 experimental units. For the present investigation a Design was used Totally at random (DCA) with eight treatments and with four repetitions, with an arrangement trifactorial 2x2x2, two brine types (S) (20%, 30%), two times of smoky (TO) (3, 6, hours) and two times of temperatures (T) (60°C, 70°C). They were also carried out descriptive statistical tests of Tukey: significance level: p <0.05, for the valuation of the organoleptic characteristics in function of the test of Kruskal Wallis, Witting, Analysis of variance of the differences for the tests bromatológicas and for the variable microbiological it was used the central tendency statistics (you mediate), to be a count parameter. As general objective he/she thought about “to Evaluate levels of brines in the different times and temperatures in the smoky one for the conservation of the quail meat.” You concluded that: 1) in the present investigation it was observed that the levels 2 of having smoked in the fatty variable reach the but high result with 2.88%, was also observed that the level 1 of temperature in the fatty variable reach the but high result with 2.75%. 2) The interaction 1x2 of Brine x smoked in the variable humidity and fat reaches the but 65 high result. 3) the level 2x1 of Brine x temperature in the variable humidity reaches the best result with and in the fatty variable he/she stood out the level 1x1. 4) it was observed that the level 2x1 of Smoky x temperature in the variable fatty% reach the best result with 2.64%. 5) it was observed that the level 1x1x2 of Brine smoked x x temperature in the Fatty variable reaches the but high result with 2.45%. 6) it was evidenced acceptable levels of aerobics misfiles with 9.8 x 103 (UFC/g o cm3) being these levels inside that allowed for consumption of smoky quails. And 7) The treatment 6 reached the biggest gross incomes, net profits and……………………….